SPECIFICS OF TEACHING RUSSIAN AS A NON-NATIVE LANGUAGE IN SECONDARY SCHOOL: METHODOLOGICAL AND COMMUNICATIVE APPROACHES - Rajabova Irina Taxirovna,Mahmudova Surayyo Sunnatillayevna (International Journal of Literature and Language Studies, 2026)
This article examines the specifics of teaching Russian as a non-native language in secondary school. The study analyses the linguistic, psychological, and methodological challenges that characterise this educational context and identifies the factors that distinguish Russian language instruction in national schools from teaching in native-language environments. Special attention is given to the communicative barrier — the gap between students' grammatical knowledge and their ability to use the language in real communication — as one of the central problems in this field. The article argues that effective teaching of Russian as a non-native language requires a methodology that goes beyond grammar instruction and addresses the communicative, cultural, and psychological dimensions of language acquisition. A set of practical approaches is proposed, including communicative practice, audiovisual exposure, role-based activities, and the development of inner speech. The study concludes that the specifics of the national school context demand a purposefully designed methodological system that fosters both linguistic accuracy and communicative confidence.